2019
DOI: 10.1016/s2468-1253(19)30227-4
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of atherosclerotic cardiovascular disease in people with hepatitis C virus infection: a systematic review, meta-analysis, and modelling study

Abstract: Background More than 70 million people worldwide are estimated to have hepatitis C virus (HCV) infection. Emerging evidence indicates an association between HCV and atherosclerotic cardiovascular disease. We aimed to determine the association between HCV and cardiovascular disease, and estimate the national, regional, and global burden of cardiovascular disease attributable to HCV. Methods For this systematic review and meta-analysis, we searched MEDLINE, Embase, Ovid Global Health, and Web of Science database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 80 publications
3
86
0
5
Order By: Relevance
“…In conclusion, data from this study show that HCV clearance significantly reduces the risk of major CV events. Our finding has a great clinical impact since in 2015 it was estimated that around 71 million people worldwide are still infected, and it has been evaluated that 1.5 million (95% CI 0.9-2.1) disability-adjusted life-years (DALY) from cardiovascular diseases are to be attributed to chronic HCV infection [26]. Therefore, HCV clearance has advantages both in prognostic and clinical terms and has a significant impact on public health with savings on healthcare costs.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In conclusion, data from this study show that HCV clearance significantly reduces the risk of major CV events. Our finding has a great clinical impact since in 2015 it was estimated that around 71 million people worldwide are still infected, and it has been evaluated that 1.5 million (95% CI 0.9-2.1) disability-adjusted life-years (DALY) from cardiovascular diseases are to be attributed to chronic HCV infection [26]. Therefore, HCV clearance has advantages both in prognostic and clinical terms and has a significant impact on public health with savings on healthcare costs.…”
Section: Discussionmentioning
confidence: 87%
“…Chronic HCV infection is associated with an increased risk of atherosclerotic cardiovascular diseases [26]. There is a wide literature supporting that HCV infection increases the subclinical and clinical risk of CV diseases [2][3][4][5][6][7][8][9][10][11] through multiple direct and indirect proatherogenic immune and inflammatory mechanisms, metabolic alterations (insulin resistance, diabetes) and a direct cardiovascular tropism of HCV [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot tell whether nonalcoholic cirrhosis or alcoholism is associated with MI in the same temporal way. Concerning other aetiologies, cumulated evidence suggests that chronic hepatitis C is associated with MI, in support of a relationship between liver disease and MI.…”
Section: Discussionmentioning
confidence: 92%
“…4 Chronic viral diseases, in particular human immunodeficiency virus (HIV), have been strongly linked to the development of clinical cardiac diseases. 5,6 Chronic HCV infection (CHC) has been linked to subclinical and clinical cardiovascular diseases (CVD), such as myocardial infarctions, congestive heart failure, cerebrovascular accident (CVA), and peripheral arterial disease, 7 and proposed mechanisms include chronic inflammation and immune activation driven by HCV infection as well as direct endothelial invasion and dysfunction. Studies have shown increased prevalence of certain cardiac biomarkers associated with increased CVD risk in patients with CHC compared to age-matched uninfected patients.…”
Section: Introductionmentioning
confidence: 99%